Storefront Health Protocol IoT System Using Using Raspberry Pi Camera and Haar Cascade Classifier - I Gede Bagus Wirawan; I Gede Putu Wirarama Wedashwara; Ahmad Zafrullah Mardiansyah (Journal of Computer Science and Informatics Engineering (J-Cosine), 2022)
The Covid-19 health protocol is a regulation by government to feel safer doing activities during Covid-19 pandemic. Generally, spread of Covid-19 occurs in public places, one of which is a shop. By building an IoT tool that is expected to be able to detect early on the potential for someone to contract Covid-19 by detecting body temperature and mask when entering a store. Shop owners can see people who have the potential for Covid-19 and customers who are wrong/not wearing masks, using IoT functions to send data between sensors so that shop owners can monitor website-based systems. From the test results, the success rate of tools and algorithms is 78.38% of data that successfully detects temperature and masks, then there are 29.62% of data that fail to detect masks and temperatures. The data is then recorded in a JSON file which will be displayed into a website-based information system.